Analysis of Predicted Kappa Number and Viscosity in Oxygen Delignification of Manihot Esculenta Crantz - Ni'mah, Hikmatun; Wulansari, Safitri; Bazliah, Dinda; Darmawan, Aria; Roesyadi, Achmad; Kurniawansyah, Firman (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2024)
The oxygen delignification of cassava stem waste (Manihot esculenta crantz) kraft pulps were studied under vary conditions. Kappa number and viscosity are two important parameters for the quality of resulting pulp, which are influenced by some operation conditions. Therefore, it is important to observe and examine the Kappa number and viscosity beforehand. The aim of this study was to obtain a prediction of the Kappa number and viscosity for various conditions and to obtain the excellent condition for producing qualified pulp. The prediction was carried out by governing kinetic model of oxygen delignification reaction from experiment data. Based on analysis of prediction, the optimum condition was reached at pressure of 2 bar, alkali charge of 2%, temperature of 80 oC, and reaction time of 53 minutes with pulp viscosity of 878.73 ml/g. In addition, the experimental data matched well to the prediction data obtained from kinetic model.